Sistem Pakar Diagnosa Tumor Wilms Menerapkan Metode Hybrid Case Based Dan Anfis - Indrimina Halawa (STMIK Budi Darma, 2021)
Wilms tumor is a type of kidney tumor that affects children aged 3-4 years, especially boys. These tumors generally only attack one kidney, but it does not rule out the tumor can attack both kidneys in the child's body. This tumor is a kidney tumor that is most often experienced by children compared to other types of tumors. An expert in the field of Wilms tumor diagnosis is a person who has special abilities in the field of Wilms tumor diagnosis which knowledge is rarely owned by others so that the services of an expert in this field are indispensable for those with Wilms tumor. Due to the lack of experts in the field of Wilms tumor diagnosis, long queues often occur at a Wilms tumor diagnosis expert practice place for consultation so that an expert must take a lot of time to provide services to patients who come with Wilms tumor consultation. To overcome this problem, a system that is able to represent an expert is needed to diagnose Wilms tumor with the same capabilities as the expert, namely an expert system. Therefore, in the research the authors built an expert system for Wilms tumor diagnosis using vbnet 2008, to get an accurate diagnosis, the Hybrid Case Based and Rule Based Reasoning methods were applied. The results of this study can later be used to diagnose tumor wilms on a personal computer by employees who help expert activities. With this system, it is hoped that the consultation process for Wilms tumor diagnosis at an expert's practice place will be more effective and efficient.